Mechanistic roles of neutrophil heterogeneity in tumour pathogenesis - Lin, Hua; Liao, Yutian; Chen, Zhonghui; Chen, Ye; Chen, Yating; Wang, Yulin; Chen, Zhanfei (Frontiers in Immunology, 2025)
Neutrophils are the body’s primary responders to infection and injury, yet they also exert diverse effects within tumours through distinct subtypes and mechanisms of action. In light of persistent challenges in clinical oncology, including drug resistance, a research focus on neutrophil biology represents a promising frontier. This review examines neutrophil heterogeneity in cancer by exploring their developmental stages, tumour-specific mechanisms influencing progression, and established classification systems. It further highlights emerging neutrophil subpopulations identified across specific tumours and disease contexts, offering insights into their dual roles in pathogenesis. By integrating recent findings, this work provides a framework to guide drug development and clinical therapeutics in oncology and related pathologies.